Hepatitis C treatment - better outcomes through partner support - Chapman, Fleur; McManus, Alexandra (Australasian Medical Journal Pty Ltd, 2012)
BACKGROUND Globally, it is estimated that 170 million people are living with hepatitis C and between three and four million are newly infected annually. In Australia, around 1% of people are living with chronic hepatitis C, with two-thirds of these being men. AIMS This research aimed to determine the impact of hepatitis C treatment on partners of patients using in-depth exploratory techniques. METHOD Four infected men and their partners (n= 8 participants) and three service providers were recruited and interviewed separately to identify the needs of female partners supporting patients with Hepatitis C. Discussion was based on the experiences of female partners during the treatment phase of male hepatitis C patients. RESULTS All participants recognised a need for greater assistance for partners of hepatitis C treatment patients. It was also recognised that strong social support improved treatment outcomes and helped to maintain the survival of family relationships during the intensive treatment phase. CONCLUSION Although this research was limited by size, it provides valuable insights into ways to enhance hepatitis C management outcomes beyond traditional medical treatment regimes, for example through formal partner support.